Production of Green Hydrogen in Bangladesh and its Levelized Cost (Dhaka University Journal of Applied Science and Engineering, 2022)
Hydrogen is an excellent source of energy that can be burnt directly and used in fuel cells with no emission to environment. In recent years, green hydrogen has become a research interest in many developed and developing countries. The main barrier to this green fuel is the production cost. Production of hydrogen using solar photovoltaic (PV) powered water electrolysis process might reduce the production cost. This paper presents the determination of the Levelized cost of hydrogen (LCOH) produced from a PV-based electrolysis plant which is built in Energy Institute, Dhaka University. The analysis uses LCOH and Life Cycle Cost (LCC) methods to determine the production cost of hydrogen. HOMER Energy software has been used to determine the electricity cost. The plant's lifetime is assumed to be 25 years, with a discount rate of 5%. The Levelized electricity cost from the invested Solar PV plant is about BDT 37.92, and the pay back period is about four years. The electricity consumption of the hydrogen generating plant is 4225 kWh/year, and the amount of hydrogen yield is 128520 kg/year. It is found that the LCOH of green hydrogen is BDT 3.41/kg by LCOH method and BDT 6.79/kg by LCC. The determined cost is very competitive concerning the international market price which is about US$13.99/kg. If production cost becomes comparatively lower, Bangladesh could become a remarkable green hydrogen producer with a remarkable impact in the international market. The model and analysis might help to design, assess and implement such projects in Bangladesh and establish a green hydrogen economy.DUJASE Vol. 6 (2) 64-71, 2021 (July)